2016
DOI: 10.1080/17458080.2016.1178401
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor quantum dots as nanoelectronic circuit components

Abstract: In this paper, a systematic investigation of frequency response of CdS and CdS:Cu quantum dot devices, following microwave-assisted synthesis, is presented. Phase of the output relative to the input as a function of frequency is also recorded to have some insight into the observed low-pass filter characteristics of the as-fabricated devices. The as-fabricated quantum dot devices are found to have all the characteristics of a classical low-pass filter with optimization of gain, phase shift and cut-off frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The W-H plot for CdS and CZ5 is given in figures 4(a) and (b) respectively. Lattice parameters 'a' and 'c' for CdS and CdS/ZnS (1:5) samples are calculated using equation (3).…”
Section: Results and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The W-H plot for CdS and CZ5 is given in figures 4(a) and (b) respectively. Lattice parameters 'a' and 'c' for CdS and CdS/ZnS (1:5) samples are calculated using equation (3).…”
Section: Results and Data Analysismentioning
confidence: 99%
“…Semiconductor QDs of II-VI group have been attractive over the years to researchers due to their fascinating optical and electronic properties. CdS and ZnS are important II-VI semiconductors with a wide variety of applications in solar cells [1], light-emitting diodes [2], electronic RF filers [3], phosphors, optical sensors [4], optoelectronic devices and flat-panel displays [5] etc as well as has potential applications in biomedical field [6]. The emerging composite materials can be synthesized in the form of ternary, quaternary, or in core/shell type through manipulation of growth parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their small-scale sizes, the quantum dots exhibit interesting behaviors and properties like real atoms because of the effects of the spatial confinement on charge carriers. These properties have been intensively investigated both experimentally and theoretically and have led to a wide applications range [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Organic light emitting diode displays with QD color filters have recently been suggested as future display technology, and red, green, and blue QD color filter arrays are used to achieve a three-primary-color emission . Numerous studies have recently reported the fabrication of QD arrays with controllable size, shape, and composition. QD arrays can be used not only in display technologies but also in nanoelectronics, optoelectronics, telecommunication devices, and quantum computing . Thus, large-area QD arrays fabricated with multiple types of QDs are a highly useful and promising technology .…”
Section: Introductionmentioning
confidence: 99%
“…5 Numerous studies have recently reported the fabrication of QD arrays with controllable size, shape, and composition. 6−10 QD arrays can be used not only in display technologies but also in nanoelectronics, 11 optoelectronics, 12 telecommunication devices, 13 and quantum computing. 14 Thus, large-area QD arrays fabricated with multiple types of QDs are a highly useful and promising technology.…”
Section: ■ Introductionmentioning
confidence: 99%